2008
DOI: 10.1128/jb.01857-07
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Enhances the Survival of Mycobacterium tuberculosis during Inhibition of Respiration

Abstract: When oxygen is slowly depleted from growing cultures of Mycobacterium tuberculosis, they enter a state of nonreplicating persistence that resembles the dormant state seen with latent tuberculosis. In this hypoxic state, nitrate reductase activity is strongly induced. Nitrate in the medium had no effect on long-term persistence during gradual oxygen depletion (Wayne model) for up to 46 days, but significantly enhanced survival during sudden anaerobiosis. This enhancement required a functional nitrate reductase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 34 publications
3
83
1
3
Order By: Relevance
“…The specific biochemical conditions encountered by M. tuberculosis in the host are complex and heterogeneous (3, 4, 7, 9, 10). Nitrate is a natural component of human body fluids that arises in part from dietary sources and in part as a terminal autooxidation product of the nitric oxide produced by the three isoforms of nitric oxide synthase in diverse cells, including immune-activated smooth muscle, epithelial cells, and hematopoietic cells, such as macrophages infected with M. tuberculosis (11,15,(43)(44)(45). Both nitric oxide and hypoxia increase M. tuberculosis nitrate reductase activity at the whole cell level.…”
Section: Metabolic Essentiality Of Succinate Dehydrogenase Activity Inmentioning
confidence: 99%
“…The specific biochemical conditions encountered by M. tuberculosis in the host are complex and heterogeneous (3, 4, 7, 9, 10). Nitrate is a natural component of human body fluids that arises in part from dietary sources and in part as a terminal autooxidation product of the nitric oxide produced by the three isoforms of nitric oxide synthase in diverse cells, including immune-activated smooth muscle, epithelial cells, and hematopoietic cells, such as macrophages infected with M. tuberculosis (11,15,(43)(44)(45). Both nitric oxide and hypoxia increase M. tuberculosis nitrate reductase activity at the whole cell level.…”
Section: Metabolic Essentiality Of Succinate Dehydrogenase Activity Inmentioning
confidence: 99%
“…Nitrate is a physiologic component of human body fluids, where it arises from the diet and from autooxidation of the NO produced not only by iNOS (NOS2) but also by the constitutively expressed enzymes NOS1 and NOS3. Studies in which nitrate was furnished in vitro revealed that Mtb's ability to respire nitrate allows it to better withstand acid, nitrosative stress (27), or sudden anaerobiosis (28). The evolutionary success of "modern" Mtb strains, which are more prevalent than "ancestral" strains, has been attributed to their enhanced nitrate reductase activity (29,30).…”
mentioning
confidence: 99%
“…M. tuberculosis uses anaerobic electron sinks such as nitrate and possibly fumarate (9,10). In contrast to the pathogen, M. smegmatis lacks a functional nitrate reductase (10,11), and it is unclear if one of the putative succinate dehydrogenase/fumarate reductase operons (9, 12) acts as a fumarate reductase.…”
mentioning
confidence: 99%
“…M. tuberculosis uses anaerobic electron sinks such as nitrate and possibly fumarate (9,10). In contrast to the pathogen, M. smegmatis lacks a functional nitrate reductase (10,11), and it is unclear if one of the putative succinate dehydrogenase/fumarate reductase operons (9, 12) acts as a fumarate reductase. However, it can scavenge oxygen using a cytochrome bd complex that is upregulated under hypoxia (13,14) and can enhance its metabolic plasticity using three phylogenetically distinct [NiFe]-hydrogenases for both hydrogen oxidation and possibly hydrogen production (15).…”
mentioning
confidence: 99%